Individual-level factors related to better mental health outcomes following child maltreatment among adolescents. (May 2018) - Cheung, Kristene; Taillieu, Tamara; Turner, Sarah; Fortier, Janique; Sareen, Jitender; MacMillan, Harriet L.; Boyle, Michael H.; Afifi, Tracie O.
Abstract: Research on factors associated with good mental health following child maltreatment is often based on unrepresentative adult samples. To address these limitations, the current study investigated the relationship between individual-level factors and overall mental health status among adolescents with and without a history of maltreatment in a representative sample. The objectives of the present study were to: 1) compute the prevalence of mental health indicators by child maltreatment types, 2) estimate the prevalence of overall good, moderate, and poor mental health by child maltreatment types; and 3) examine the relationship between individual-level factors and overall mental health status of adolescents with and without a history of maltreatment. Data were from the National Comorbidity Survey of Adolescents (NCS-A; n = 10, 123; data collection 2001–2004); a large, cross-sectional, nationally representative sample of adolescents aged 13–17 years from the United States. All types of child maltreatment were significantly associated with increased odds of having poor mental health (adjusted odds ratios ranged from 3.2 to 9.5). The individual-level factors significantly associated with increased odds of good mental health status included: being physically active in the winter; utilizing positive coping strategies; having positive self-esteem; and internal locus of control (adjusted odds ratios ranged from 1.7 to 38.2). Interventions targeted to adolescents with a history of child maltreatment may want to test for the efficacy of the factors identified above.